PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK THINK PAIR SQUARE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP N 2 RANAH PESISIR - Yuneta, Rahma; Delsi K, Delsi K; febriana, Rian (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research is background of by students that not ordinary learning did not give the result yet that maximum, the concept of mathematic students undestanding still low. The purpose of this research in for knowing about what did mathematic students concept understanding of used the model of cooperative learning technique of think pair square is better than model of mathematic concept the students used convensional learning. The kind of this research is experiment with research random plan to subject. The instrument was used on this research was essey test. The risult of try of hyphotesis test useofÂ the t test swith help the software MINITAB was got P-value smaller than real plan alpha was 0,004<0,05. So, hyphothesis was receive. So can be summarise that students math ability that used learning model of cooperative technique of think pair square better than convensional learning to class VIII SMPN 1 Ranah Pesisirof faith 95%.Â